2011
DOI: 10.1007/s10147-011-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

ATP assay-guided chemosensitivity testing for gemcitabine with biopsy specimens obtained from unresectable pancreatic cancer using endoscopic ultrasonography-guided fine-needle aspiration

Abstract: Chemosensitivity testing by use of EUS-FNA samples in patients with unresectable pancreatic cancer is feasible. This definition emphasizes the possibility of selecting patients for whom favorable results from gemcitabine treatment can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…First, EUS-FNA often requires the presence of an on-site cytopathologist to assess the adequacy of samples and improve diagnostic yield. [25][26][27] is also useful in providing a histologically complete specimen for evaluation of tumor biology with a higher diagnostic accuracy than samples collected by EUS-guided FNA. [22][23][24] Lastly, EUS-FNA is associated with a low negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…First, EUS-FNA often requires the presence of an on-site cytopathologist to assess the adequacy of samples and improve diagnostic yield. [25][26][27] is also useful in providing a histologically complete specimen for evaluation of tumor biology with a higher diagnostic accuracy than samples collected by EUS-guided FNA. [22][23][24] Lastly, EUS-FNA is associated with a low negative predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy dose escalation for this subset of patients may delay or prevent recurrence, and thereby improve survival. Another possibility would be to test tumor tissue obtained at the time of biopsy for radiosensitivity, similar to a recent study that evaluated sensitivity to gemcitabine in vitro [25], to select patients most likely to benefit from aggressive local therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that CA 19–9 levels can predict response to CRT and can be prognostic for outcome in the unresectable setting [11,25,27,28]. Yoo et al [11] recently demonstrated that a CA 19–9 level <100 U/mL before or after CRT for unresectable pancreatic cancer is prognostic for overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tissue specimens for histological examination also provide the opportunity (i) to easily immunostain the tissue, further improving differential diagnostic capabilities; (ii) to reach a specific diagnosis for benign diseases not always possible with a cytological sample, thus sparing patients from more invasive and risky procedures or costly and unnecessary follow up examinations; (iii) to potentially perform tissue profiling and/or cell culture needed to guide targeted therapies for individualized treatment of patients with cancer of the gastrointestinal tract [7][8][9].…”
Section: Introductionmentioning
confidence: 99%